Contamination Associated With Glove Changing Techniques in the Operating Theatre - Boekel, Pamela; Ek, Eugene T. (Frontiers in Surgery, 2022)
Background Sterility of the operative field during surgery is imperative in reducing the risk of infection. Most commonly, double gloves are worn by surgeons. When contamination occurs, the top gloves are changed intra-operatively. No studies have investigated which glove changing technique is best. Therefore, in this study, we aim to identify which top glove changing technique causes the least surface contamination. Methods Glitterbug™ (UV fluorescent powder) was applied to the top gloves of 3 individuals who changed their top gloves according to a randomised method – Method 1: 3 pairs worn, remove the outer pair; Method 2: 2 pairs worn, remove the top glove, replace unassisted; and Method 3: 2 pairs worn, remove the top glove, and replace assisted by a scrub nurse. A blinded investigator inspected for Glitterbug™ contamination under UV light. Results Two hundred and ten trials were performed and two types of contamination were identified, namely, direct contact and airborne spread. For absolute contamination, Method 1 had 59/64 (92%) contaminated trials, Method 2 had 49/65 (75%) contaminated trials, and Method 3 had 64/81 (79%) contaminated trials. This was statistically significant (p = 0.031). For direct contamination only, Method 1 had 38/64 (59%) contaminated trials, Method 2 had 24/65 (37%) contaminated trials, and Method 3 had 20/81 (25%) contaminated trials. This was statistically significant (p < 0.0001). Conclusions Method 2 had a statistically significant lower contamination rate overall, with Method 3 having the lowest direct contamination rate. We believe that wearing 2 gloves, removing the top glove and replacing it, either assisted or unassisted, could decrease surface contamination of the sterile field.